Pancasila Sebagai Fondasi Pendidikan di SMA Negeri 3 Medan - Chindy Eskana Nababan; Liesna Andriany (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Pancasila as the foundation of the Indonesian state, has an important role in shaping national identity and directing national development. In the context of education, Pancasila has great potential to become a strong foundation in shaping the character of the younger generation and building a cultured, democratic and just society. This research aims to examine the role of Pancasila as the foundation of Indonesian education. This research aims to find out how Pancasila is the foundation of education at SMA NEGERI 3 MEDAN. This type of research uses descriptive qualitative research. Based on the research results, it can be found that the implementation of Pancasila values has been embedded for a long time in SMA N 3 MEDAN, especially in class XI IPA 1. The results of this research are expected to provide a better understanding of the role of Pancasila as the foundation of Indonesian education and the importance of implementing Pancasila values.This research also provides a basis for developing educational policies that are more holistic and include aspects of character and values in the learning process. In this way, it is hoped that Indonesia's young generation can grow and develop in accordance with the values of Pancasila, so that they are able to build a harmonious and just society.